Pemanfaatan Aplikasi Canva sebagai Media Pembuatan Poster Digital untuk Meningkatkan Kreativitas Siswa Kelas Viii pada Mata Pelajaran Seni Budaya di SMP Negeri 24 Banjarmasin - Amanda, Syaraya; Jumadi, Jumadi; Sufyadi, Susanti (EduInovasi: Journal of Basic Educational Studies, 2024)
The 4.0 industrial revolution encourages teachers and students to understand technology in order to improve the quality of education. However, teachers face challenges in integrating technology into learning, especially due to limitations among students. In this research, the Canva application was used to enhance the effectiveness of learning and address existing constraints. The reasearch method employed descriptive analysis with quantitative approach, using instruments such as assessment rubrics, student creativity questionnaires, and documentation. The research results indicate that before using the Canva application, the average creativity of students fell within the category of “Moderately Creative” with a percentage of 59,6%. After using Canva, student creativity increased by 14.2%, with an average percentage reaching 73,9% in the “Creative” category. Furthermore, their performance in creating digital posters achieved a score of 89,2%, which falls into the “Very Good” category as it is within the range of 80%-100%. This demonstrates that the Canva application serves as a useful tool for creating digital posters and can enhance student creativity.